An Image Authentication Based on Discrete Fourier Transform - Kieu, Duc; chang, Chin-Chen (My University, 2011)
The advances of network technologies and digital devices facilitate users to exchange multimedia data over the public networks. However, this also raises significant concerns about how to protect sensitive multimedia data from being illegally copied and unauthorized modifications. Thus, this paper proposes a fragile watermarking method to detect illegitimate alterations of the watermarked data. The proposed method embeds a grayscale watermark image into a grayscale cover image in a block-by-block manner by using discrete Fourier transform. Experimental results show that the proposed method can successfully and exactly detect and localize any tampered regions of the watermarked image.
Keywords: Network Technologies; watermarking method; fourier transform